2016
DOI: 10.1007/s40610-016-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell Mechanosensitivity Is Enabled by the LINC Nuclear Complex

Abstract: Mechanoresponses in mesenchymal stem cells (MSCs) guide both differentiation and function. In this review, we focus on advances in0 our understanding of how the cytoplasmic cytoskeleton, nuclear envelope and nucleoskeleton, which are connected via LINC (Linker of Nucleoskeleton and Cytoskeleton) complexes, are emerging as an integrated dynamic signaling platform to regulate MSC mechanobiology. This dynamic interconnectivity affects mechanical signaling and transfer of signals into the nucleus. In this way, nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 161 publications
(212 reference statements)
1
37
0
Order By: Relevance
“…Cells must sense, respond, and adapt to their physical environments at every level (molecular, cellular, tissue, organ and organism). Cells respond to mechanical cues by initiating signals that result in adaptations in cytoskeletal architecture and gene expression [ 46 ]. Adhesion to the ECM is achieved by all types of adherent cells.…”
Section: Adhesion Of Cells To Ecm and Mechanotransductionmentioning
confidence: 99%
“…Cells must sense, respond, and adapt to their physical environments at every level (molecular, cellular, tissue, organ and organism). Cells respond to mechanical cues by initiating signals that result in adaptations in cytoskeletal architecture and gene expression [ 46 ]. Adhesion to the ECM is achieved by all types of adherent cells.…”
Section: Adhesion Of Cells To Ecm and Mechanotransductionmentioning
confidence: 99%
“…FHOD1 formin 51 , for example, has recently been shown to interact with Nesprin-2 and may be important for nuclear positioning and maintaining coupling between the nucleus and cytoskeleton. Further, LINC complexes may also be involved in formin mediated perinuclear and intranuclear actin dynamics 52 53 , suggesting that formins play a yet to be determined role in LINC mediated LIV mechanotransduction. Our data demonstrated that the expression levels of Nesprin-2, the actin-binding element of the LINC complex as well as the nuclear scaffolding protein LaminA/C experienced the greatest upregulation at Day 14 when exposed to horizontal 100 Hz-0.15 g LIV.…”
Section: Discussionmentioning
confidence: 99%
“…The LINC complex was discovered relatively recently, but has been shown to be highly conserved in eukaryotes, with myriad functions as described in numerous reviews [4][5][6][7][8][9]. These LINC-mediated functions include regulation of nuclear shape and position [10,11], mechanosensory signal transduction [12], control of cell division, intranuclear architecture and gene regulation [13][14][15], and the specialized behavior of meiotic chromosomes to ensure segregation and fertility [16][17][18]. The two core LINC components are the inner nuclear membrane (INM) SUN-domain proteins [19,20] and outer nuclear membrane (ONM) KASH-domain proteins [21].…”
Section: Introductionmentioning
confidence: 99%